2005
DOI: 10.1093/jurban/jti087
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Events in New Jersey After the September 11, 2001, Terrorist Attack

Abstract: The higher stress associated with the World Trade Center (WTC) attacks on September 11, 2001, may have resulted in more cardiac events particularly in those living in close proximity. Our goal was to determine if there was an increase in cardiac events in a subset of emergency departments (EDs) within a 50-mi radius of the WTC. We performed a retrospective analysis of consecutive patients seen by ED physicians in 16 EDs for the 60 days before and after September 11 in 2000-2002. We determined the number of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…The role of acute mental stress as a trigger of cardiovascular events is, however, well established. Our findings are indeed in line with findings from a number of studies indicating an immediate increase in cardiovascular morbidity or mortality following stressful events, such as natural disasters,3 4 war or terrorism,5 6 the diagnosis of a life-threatening disease,7 8 loss of a child9 and major sporting events 10. Furthermore, Stuckler and coworkers11 reported a 6.4% increase in male cardiovascular mortality during the first year following banking crises in 19 high-income countries; the study did not address female cardiovascular morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…The role of acute mental stress as a trigger of cardiovascular events is, however, well established. Our findings are indeed in line with findings from a number of studies indicating an immediate increase in cardiovascular morbidity or mortality following stressful events, such as natural disasters,3 4 war or terrorism,5 6 the diagnosis of a life-threatening disease,7 8 loss of a child9 and major sporting events 10. Furthermore, Stuckler and coworkers11 reported a 6.4% increase in male cardiovascular mortality during the first year following banking crises in 19 high-income countries; the study did not address female cardiovascular morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…It was determined that there was a significant 49% increase in the cases admitted to hospitals. This study indicates that the high stress levels experienced as a result of the disaster may have contributed to an elevation in the level of heart attack cases in New Jersey (Allegra et al 2005).…”
Section: Other States/ Adult Populationmentioning
confidence: 79%
“…12 Two studies examined outcomes to 60-days; a study of 16 hospitals in New Jersey found a 49% increase (p=0.01) in the incidence of AMI in the 60 days following the event (42% when the number of patients presenting to the ED was controlled for). 14 A study of admissions to the telemetry and coronary care units at a single center in Brooklyn also identified an increase in the overall occurrence of cardiac events in the post-exposure period compared to the corresponding period in 2010 (p=0.008). 13 Interestingly, the incidence of AMI and tachyarrhythmia was increased following the event, however, the incidence of admission for unstable angina did not change.…”
Section: Resultsmentioning
confidence: 96%
“…10, 12, 13, 18, 19, 21, 23, 26, 28 This is particularly apparent when considering studies of the September 11 th terrorist attacks since many patients did not report to work in Manhattan in the weeks after the event, altering the daily hospitalization patterns of patients both in the city and in the surrounding areas. 1214 As almost all studies utilized historical controls from the previous year, the comparison population was generally similar to the exposed population. Comparability of the groups was not always well reported, and was particularly concerning for the three studies describing the effects of long-term conflict on the population.…”
Section: Resultsmentioning
confidence: 99%